A DSM-based project-scheduling system for collaborative product development. (17th December 2007) - Lin, Ming-Chyuan; Chen, Kuohsiang; Chang, Wunching; Chen, Chun-Hsien
Scheduling and managing a collaborative New Product Development (NPD) process for large projects is a difficult exercise that requires much effort and experience. This paper presents a prototype web-enabled scheduling system that incorporates Design Structure Matrix (DSM) to support NPD projects in a collaborative product development environment. The prototype system is implemented on the internet, based on an agent architecture. Basically, it is able to assist collaborative NPD projects in obtaining an appropriate execution sequence of project tasks, generating a project schedule effectively, monitoring the development process, and handling the dynamic events such as task delay and iteration. An illustrative example is provided.